Three new additions to the earthworm (Clitellata: Megadrili) fauna of Kerala state from the Western Ghats biodiversity hotspot, south-western India - Narayanan, Sasankan Prasanth; Paliwal, Rahul; Thomas, Basil; Thomas, Ambattu Paili; Julka, Jatinder Mohan (Opuscula Zoologica Instituti Zoosystematici et Oecologici Universitatis Budapestinensis, 2024)
n India, studies on above-ground biodiversity have received more attention than those on below-ground biodiversity. With this view, systematic surveys for earthworms were carried out in the Western Ghats mountain range of Kerala state in southwestern corner of Peninsular India. This research resulted in three new records for the state, viz. Drawida nandiensis Stephenson, 1924, D. nepalensis Michaelsen, 1907 and Celeriella bursata Jamieson, 1977. Among these, D. nandiensis and D. nepalensis, are recorded for the first time from the Western Ghats biodiversity hotspot. Previously D. nandiensis and C. bursata were known only from their respective type localities. With the addition of three species the total number of earthworm taxa reported from Kerala state has raised to 128 and now the Western Ghats mountain ranges has 271 species of earthworms.